COMPARATIVE ANALYSIS OF COGNITIVE METAPHORS IN RUSSIAN AND ENGLISH: LINGUOCULTURAL AND LINGUOCOGNITIVE ASPECTS - Каримова Оминахон Махмудовна; Арустамян Я. Ю. (Bright Mind Publishing, 2025)
This work is a comparative analysis of cognitive metaphors in the Russian and English languages, with special attention to their cultural and cognitive features. Based on scholarly articles, dictionaries, and literary texts, the study uses the descriptive-comparative method to examine how metaphorical concepts are structured and interpreted in each language. The analysis shows that, despite the presence of universal metaphorical models based on common human experience, cultural characteristics play a key role in the formation of metaphorical thinking. Russian metaphors tend to emphasize internal, spiritual, and emotional experiences, reflecting a worldview focused on introspection and collective identity. Whereas English metaphors tend to emphasize clarity, functionality, and objectivity, which fits a more pragmatic and individualistic cultural attitude. These differences are viewed through the lens of conceptual mapping and cognitive theory, which contributes to a deeper understanding of the relationship between language, thought and culture.
Keywords: Cognitive metaphor, cultural differences, conceptual mapping, linguistic worldview, metaphorical models, language and thinking.